CITRA MEREK DAN PROMOSI SEBAGAI VARIABEL PENTING UNTUK MENINGKATKAN KEPUTUSAN PENGGUNAAN TRANSPORTASI GRAB ONLINE DI KABUPATEN GIANYAR - I Wayan Meryawan; Wirya Gupta (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2021)
Building an increase in online transportation users can be done by increasing the brand image and conducting online and offline promotional activities. One of the most popular applications today is PT. Gojek Indonesia, Gianyar branch. The purpose of the study was to determine the effect of brand image and promotion partially and simultaneously on the decision to use Gojek Online transportation by using a sample in this study of 98 respondents from the Gojek application user community in Gianyar Regency which were taken representatively. The data analysis technique used multiple linear regression analysis, t test, F test, and determination test. The results of multiple linear regression analysis Y= 1.124 + 0.162 X1 + 0.967 X2 with positive results. The results of the t-test show that partially brand image and promotion have a positive and significant effect where the result of the t-test is greater than the t-table. Simultaneously shows that brand image and promotion have a positive and significant effect on the decision to use Gojek with the result that the F-count value of 206.008 is greater than the F-table value of 3.09.